2006
DOI: 10.1021/ja058303m
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of the Rotary Motion by Structural Modification in Light-Driven Unidirectional Molecular Motors

Abstract: The introduction of bulky substituents at the stereogenic center of light-driven second-generation molecular motors results in an acceleration of the speed of rotation. This is due to a more strained structure with elongated C=C bonds and a higher energy level of the ground state relative to the transition state for the rate-limiting thermal isomerization step. Understanding the profound influence that variation of the substituent at the stereogenic center holds over the rotational speed of the light-driven mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
215
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(241 citation statements)
references
References 56 publications
21
215
1
2
Order By: Relevance
“…24,44 A major experimental effort has therefore been invested in accelerating the rate-limiting thermal steps of overcrowded alkene-based rotary molecular motors, 18,19,21,[23][24][25]27,28,33 exploring the influence of conformational, steric and electronic factors. From such studies, it has been found that one way of lowering the thermal freeenergy barriers of type IIa motors is to contract the sizes of the rotator and stator by employing a cyclopenta[a]naphthalenylidene rotator and a fluorene stator, as done in type IIb motors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,44 A major experimental effort has therefore been invested in accelerating the rate-limiting thermal steps of overcrowded alkene-based rotary molecular motors, 18,19,21,[23][24][25]27,28,33 exploring the influence of conformational, steric and electronic factors. From such studies, it has been found that one way of lowering the thermal freeenergy barriers of type IIa motors is to contract the sizes of the rotator and stator by employing a cyclopenta[a]naphthalenylidene rotator and a fluorene stator, as done in type IIb motors.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Several examples of such systems known as either first-generation or second-generation rotary molecular motors are shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the chiral overcrowded alkenes reported before,48, 57, 61 the new chiral motor M1 in the present study was designed with structural modification on the rotor region (Figure 1a). As reported previously,49 the length of the rigid substituents at the 6‐position of naphthalene ring play an crucial role on the entropic barrier for rotation, but insignificantly affect the enthalpy of activation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the dynamic controllability of unidirectional rotation, the stereoselectively chiroptical inversion between the stable ( P ) form and the unstable ( M ) form is reversible with a variable half‐life by structural modification from 8 ns to 1.4 × 10 3 years 47, 48, 49, 50. The resulting tunability of geometrical charity has been significantly investigated to create photoactiving chiral catalysts in solvents51, 52 and polar switchovers on solid surfaces 53, 54, 55.…”
Section: Introductionmentioning
confidence: 99%